Cher Monsieur: Cartas A Mário De Andrade Em Francês (1920-1945): Escritores, Editores E Críticos " Organização, Fixação Do Texto E Notas - Silva, Fernanda Braz Da [UNIFESP] (2018)
This Dissertation Presents The Transcription, Edition And Notes Of The Correspondence Between Mário De Andrade (1893-1945) And Writers, Editors And Critics In The French Language. Here, There Are 16 Interlocutors Not Only From France And Brazil, But Also Francophone People From Other Nationalities. The Corpus Contains 63 Documents (Letters, Telegrams, Notes And Message Cards), Preserved In The Mário De Andrade Fund"S Correspondence Series Section, Situated In The Institute Of Brazilian Studies" Archive Of The University Of São Paulo (Ieb-Usp), Documents Which Were Sent To The Renowned Writer Of Macunaíma Between 1920 And 1945. The Purpose Of This Study Is Contributing To Brazil-France Relations Research Through The Unpublished Correspondence To Mário De Andrade Written In French, Corroborating The Point Of View Documented In Letters By Foreign Intellectuals Of The 20th Century About Brazilian Culture And Literature.